Industrial Pollution in Patna City : Physico-Chemical Analysis of Effluents and Their Effects on Water and Soil (International Journal of Scientific Research in Science and Technology, 2024)
Industrial pollution is a significant concern in Patna City, with rapid urbanization and industrial growth contributing to the degradation of natural resources. This study focuses on the physico-chemical analysis of industrial effluents and their effects on the water and soil quality in and around Patna. Effluents from various industries, including textile, sugar, rice mills, and small-scale manufacturing units, are released into nearby water bodies and soils, posing serious environmental risks. The research aims to assess the levels of pollutants by analysing key physico-chemical parameters such as pH, total dissolved solids (TDS), biochemical oxygen demand (BOD), chemical oxygen demand (COD), heavy metals (lead, chromium, cadmium), and organic contaminants in industrial effluents. Samples were collected from various locations near industrial zones and water bodies. The study also evaluated the impact of these pollutants on soil and groundwater quality. It was found that prolonged exposure to industrial effluents led to the accumulation of toxic metals in soil, reducing its fertility and altering its structure. Additionally, groundwater sources were contaminated with hazardous chemicals, making them unfit for drinking and irrigation purposes. The implementation of advanced treatment technologies and sustainable industrial practices is crucial for safeguarding the environment and public health in Patna City.